2012
DOI: 10.1364/josab.29.000867
|View full text |Cite
|
Sign up to set email alerts
|

Polarization dynamics of a multimode vertical-cavity surface-emitting laser subject to orthogonal optical injection

Abstract: We have studied the effect of orthogonal optical injection on a multitransverse-mode vertical-cavity surfaceemitting laser (VCSEL). The injection beam comes from a similar VCSEL. Our results reveal that, when the receiver operates with several strong transverse modes of parallel polarization, optical injection can induce polarization switching in all of them while only one mode is locked to the external frequency. The induced switching can occur for a very weak (a few microwatts) injected beam. Periodic oscill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Attention has been paid recently on the effects of optical injection on a special type of semiconductor laser: the vertical-cavity surface-emitting laser (VCSEL) [2][3][4][5][6][7][8][9][10]. VCSELs have demonstrated many impressive characteristics, including low threshold current, single-longitudinal mode operation, circular beam profile and easy fabrication in large two-dimensional arrays [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention has been paid recently on the effects of optical injection on a special type of semiconductor laser: the vertical-cavity surface-emitting laser (VCSEL) [2][3][4][5][6][7][8][9][10]. VCSELs have demonstrated many impressive characteristics, including low threshold current, single-longitudinal mode operation, circular beam profile and easy fabrication in large two-dimensional arrays [2].…”
Section: Introductionmentioning
confidence: 99%
“…Emission in multiple transverse modes is usually found in solitary VCSELs [11] as a result of spatial-hole burning effect [12]. The effect of single-frequency optical injection on multi-transverse mode VCSELs has been also recently studied, showing that transverse mode selection or polarization switching can appear in these systems [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Optical injection in semiconductor lasers, and particularly in vertical-cavity surface-emitting lasers (VCSELs), has been studied extensively in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. VCSELs are attractive light sources because of their compactness, low power consumption, circular output beam, dense packaging, singlelongitudinal-mode operation, fast response, and low cost [2].…”
Section: Introductionmentioning
confidence: 99%
“…Locking of the frequency of the injected (slave) VCSEL to that of the injecting (master) laser enhances the VCSEL modulation bandwidth [3,4]. Orthogonal optical injection in VCSELs, in which the polarization of the injected signal is perpendicular to the linear polarization of the VCSEL, has received a lot of attention [6][7][8][9][10][11][12][13][14][15]. It has been shown that the VCSEL switches its polarization to that of the master laser when increasing the injection strength [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation